THE CONCEPTUAL MENTAL MODEL OF EXPLANATION IN AN ARTIFICIAL INTELLIGENCE SYSTEM - Chalyi, Serhii; Leshchynska, Irina (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2023)
The subject of research is the process of formation of explanations in artificial intelligence systems. To solve the problem of the opacity of decision-making in artificial intelligence systems, users should receive an explanation of the decisions made. The explanation allows you to trust these solutions and ensure their use in practice. The purpose of the work is to develop a conceptual mental model of explanation to determine the basic dependencies that determine the relationship between input data, as well as actions to obtain a result in an intelligent system, and its final solution. To achieve the goal, the following tasks are solved: structuring approaches to building mental models of explanations; construction of a conceptual mental model of explanation based on a unified representation of the user’s knowledge. Conclusions. The structuring of approaches to the construction of mental models of explanations in intelligent systems has been carried out. Mental models are designed to reflect the user’s perception of an explanation. Causal, statistical, semantic, and conceptual approaches to the construction of mental models of explanation are distinguished. It is shown that the conceptual model sets generalized schemes and principles regarding the process of functioning of the intellectual system. Its further detailing is carried out on the basis of a causal approach in the case of constructing an explanation for processes, a statistical approach when constructing an explanation about the result of the system’s work, as well as a semantic approach when harmonizing the explanation with the user’s basic knowledge. A three-level conceptual mental model of the explanation is proposed, containing levels of concepts regarding the basic principles of the functioning of the artificial intelligence system, an explanation that details this concept in an acceptable and understandable way for the user, as well as basic knowledge about the subject area, which is the basis for the formation of the explanation. In a practical aspect, the proposed model creates conditions for building and organizing a set of agreed explanations that describe the process and result of the intelligent system, considering the possibility of their perception by the user.